Precarity and freedom : insecure lives and unequal freedom in modern times : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Politics at Massey University, Manawatū, New Zealand - Steed, Lisa (Massey University, 2020)
The normalisation of insecure work in contemporary western economies has attracted increased academic attention, leading to a plethora of critiques on the conditions of insecure work and the economic and social structures which underlie them. In this thesis, I focus on the paradoxical way freedom both legitimises and contests precarious work. I explore how freedom and precarity act as tools of coercion and governing and conversely how freedom and precarity offer potentialities for resistance and provide opportunities to challenge neoliberal norms. Within the confines of this thesis I investigate Isabel Lorey’s theory of precarisation as a governmental process, based on Foucault’s genealogical problematising of dominant narratives designed to more easily govern populations. However, I also explore aspects of Judith Butler’s account of the wider implications of a precariousness that is inherent in our existential being, reflecting a physical vulnerability that drives individuals together to form protection in order to survive. In a modern context, where our inter-dependability is often made invisible and our survivability is linked to our individual endeavour and measured by our income, precarity in the form of insecure work often has wider societal implications and is driven by an existential precariousness. These implications impact both our individual identity and social fractures which justify exploitation for some, in order to secure a more livable life for others. This rhetoric highlights the often contradictory narrative of freedom. The often resulting atomisation and disparity of precarity, also offers new and diverse opportunities to defy neoliberal subjectivities, reformulating a narrative of freedom outside the market. However, the very diverse and disparate nature of precarity does also provide a challenging context for a cohesive protest movement. Conversely precarious resistance suggests new multiple sites of resistance, again challenging a discourse of freedom that is built on homogeneity and class solidarity.
Keywords: 440404 Political economy and social change